Growth differentiation factor 15 at 3 months after an acute chest pain admission is associated with increased risk of death and cardiovascular events. (3rd October 2022) - Myrmel, G M S; Steiro, O T; Tjora, H L; Langoergen, J; Bjoerneklett, R; Skadberg, Ø; Bonarjee, V V S; Mjelva, Ø R; Vikenes, K; Omland, T; Aakre, K M
Abstract: Background: Growth differentiation factor 15 (GDF-15) is related to increased risk of death and cardiovascular events when measured at initial presentation in patients with acute chest pain. Whether follow-up measurements at 3 months provide prognostic information is unknown. Purpose: This study sought to investigate the ability of GDF-15 to predict long-term prognosis when measured 3 months after an acute chest pain admission. Methods: GDF-15 was measured at baseline and 3 months after admission in 760 patients admitted with suspected NSTEMI-ACS. NSTEMI-ACS was diagnosed in 228 (30%) patients. Patients were followed for a median of 1480 (17–2118) days. GDF-15 concentration on admission and at 3-months was skewed and therefore compared using the related samples Wilcoxon signed ranked test. A baseline GDF-15 concentration of 1200pg/ml (previously defined as the 90th percentile in a healthy population) was used to divide patients into high and low concentration groups. Kaplan-Meier plots were generated and adjusted hazard ratios were estimated using multiple Cox proportional hazard regression analysis (adjusting for age, sex, hypercholesterolemia, current smoking, diabetes, hypertension, previous myocardial infarction, eGFR <60 ml/min/1.73 m 2 and cardiac troponin T). The primary endpoint was all-cause mortality following the 3-month visit and a secondary endpoint included all-cause mortality, future AMI and heart failure hospitalization. Results: Median GDF-15 concentration on admission was 940 pg/ml (IQR: 678–1464) and similar to the concentration at 3 months: 927 pg/ml (IQR: 652–1431), p=0.183. In the high-concentration group (n=249) 45 (18%) patients died, and 62 (25%) met the secondary endpoint. In the low-concentration group (n=511) 9 (1.7%) patients died (negative predictive value: 98.2%) and 22 (4%) met the secondary endpoint (negative predictive value: 95.6%). Patients with persistently elevated GDF-15 at the 3 months follow-up visit carried the highest risk for death and cardiovascular events, followed by patients who developed high concentrations during the 3-month follow-up period. Patients with elevated levels at baseline who return to normal concentrations had similar risk as patients with low levels in both measurements (Figure 1). The Kaplan-Meier curves demonstrated an increased risk of the primary and secondary endpoint in the high concentration group (Figure 2). GDF-15 concentration >1200 pg/ml at 3 months was an independent predictor of all-cause mortality with an adjusted HR for death of 4.0 (1.7–9.5, p=0.001) and for the secondary endpoint (adjusted HR 2.9, 95% CI: 1.6–5.4, p=0.001). Conclusion: Elevated GDF-15 three months after admission due to suspected NSTEMI-ACS independently predicts long-term mortality and cardiovascular events, irrespective of GDF-15 values during admission. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Western Norway Regional Health Authority